2014
DOI: 10.1016/j.ijsu.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

‘Smart’ electronic operation notes in surgery: An innovative way to improve patient care

Abstract: We used our pilot audit to target specific information that was commonly omitted and we 'enforced' these areas using drop-down selections in electronic operation note. This study has demonstrated that implementation of an electronic operation note system markedly improved the quality of documentation, both in terms of information detail and readability. We would recommend this template system as a standard for operation note documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 3 publications
4
35
0
Order By: Relevance
“…All of the typed notes were legible; this corresponds with the results presented by Ghani, et al [14]. They found a major difference in the legibility between handwritten (66% legible) versus typed notes (100% legible) [14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…All of the typed notes were legible; this corresponds with the results presented by Ghani, et al [14]. They found a major difference in the legibility between handwritten (66% legible) versus typed notes (100% legible) [14].…”
Section: Discussionsupporting
confidence: 86%
“…They found a major difference in the legibility between handwritten (66% legible) versus typed notes (100% legible) [14]. Of the notes reviewed for this paper, 86% of the handwritten notes from our previous audit were deemed legible by our three independent reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…[41-45] Each article reported either a retrospective or prospective observational study consisting of sample sizes with less than 200 notes in each arm. All studies showed greatly improved inclusion of crucial information, such as closure details, anesthesia, and antibiotics in electronically generated notes.…”
Section: Resultsmentioning
confidence: 99%
“…[45] Four of the studies reported a significant decrease in the time to finalization of electronic notes, with electronic notes being completed in 0.115. − 0.5 days compared to 5.8 −20.7 days for dictated notes.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the need for improved database, electronic medical record systems and standardized operative note templates. Implementation of an electronic operation note system could help resolve this problem [8]. There is evidence of the superiority of computerized operation notes over hand written notes [9].…”
Section: Discussionmentioning
confidence: 99%